Technological Innovations in the Food Industry: Implications for Nutrition, Sustainability, and Consumer Behavior (International Journal of Food and Nutritional Sciences, 2021)
The food industry has undergone significant technological advancements over the years, leading to transformative effects on nutrition, sustainability, and consumer behavior. These innovations have reshaped the way food is produced, processed, distributed, and consumed, with far-reaching implications for human health, environmental sustainability, and the choices consumers make. In this article, we will explore some of the key technological innovations in the food industry and their impacts on these crucial aspects. This paper will delve deeper into the transformative technological advancements that have reshaped the food industry, exploring the implications, opportunities, and challenges that lie ahead. By understanding the dynamics at play, stakeholders can navigate the evolving landscape and harness the power of technology to shape a more resilient, inclusive, and prosperous food industry for the future